Implementasi Kurikulum Merdeka pada Muatan Lokal Bahasa Madura di MI Kabupaten Pamekasan: Pendekatan Ekologis dalam Pendidikan Karakter dan Budaya - Mochamad Arifin Alatas; Moh. Hafid Effendy; Ananda Yogi Desiana; Hollila Hilyatun Nisa (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
This study aims to analyze the implementation of the Merdeka Belajar Curriculum in the local content of the Madurese language at Madrasah Ibtidaiyah (MI) in Pamekasan Regency. The research method used is descriptive qualitative, with data collection techniques including interviews, observations, and documentation studies. The results show that the application of the Merdeka Belajar Curriculum in the local content of the Madurese language faces several challenges, including a lack of resources, teacher training, and support facilities. However, there are efforts from the school to integrate cultural values and local wisdom into the learning process. This study recommends the need for improved coordination between the local government, schools, and the community to optimize curriculum implementation and provide adequate training for teachers to effectively teach the Madurese language. The findings of this research are expected to contribute to the development of regional language education in Indonesia, particularly in the context of the Merdeka Belajar Curriculum.